La personalidad de los niños de primer año de básica elemental de la escuela fiscal de educación básica Alonso de Mercadillo de la ciudad de Loja, deducidas desde el dibujo infantil, año lectivo 2017- 2018 - Córdova Aleaga, María de los Angeles (2018)
This thesis focused on the personality of first-year elementary basic children of the fiscal School of basic education Alonso market in the city of Loja, deduced from the drawing of children, school year 2017-2018. The general objective was to characterize the types of students ' personality through child drawing. The scientific, analytical, deductive, inductive and statistical methods were used to carry out the Project. The techniques and instruments applied were the tree test, surveys aimed at parents and matching lists that were applied to a total of 29 children 5 to 6 years’ old who helped to observe the daily behavior of the students in the school. The main findings were children with levels of impulsivity, in some cases the presence of egocentricity, considerable levels of aggression, children with low self-esteem, children with characteristics of inversion but with great levels of affection and imagination and development of their creativity, more than 60% of the students have appropriate social skills and education according to the development environment, also found Lower percentages of students who have difficulty in socializing and adapting to changes, insecurity and lack of affection on the part of their families that affects the daily behavior of the students because they lack the affection and security in themselves. In conclusion, it can be determined that there are significant percentages of children who require care in their homes to strengthen their self-esteem, autonomy, confidence, security among other aspects, and it is also considered important to create environments Suitable both at home, where education and training in values come from. As in educational institutions that favor an appropriate personal development of children in all their areas and thus strengthen their progress as a human being and above all as a unique and different individual in society, and thus form people with necessary values and appropriate education that promote the development of the society in which they unfold.